Gender Differences in Work-Family Balance Factors - Chai, Sian Yi; Zaiton, Hassan; Abang Ekhsan, Abang Othman (Faculty of Cognitive Sciences & Human Development UNIMAS, 2015)
Influx of women in the paid labor force had been identified as one of the important factors in raising awareness about work-family balance in organizations in developed countries in the west. The same phenomenon also occurs in Malaysia. Malaysia is considered as having traditional gender role ideology, whereby men and women have separate role in the workplace and in the family. Specifically, this study aims to identify whether there are differences in perception between men and women in public sector towards factors associated with work-life balance. Work-life balance factors examined in this study are work demands, supervisor support, organization’s family-friendly policies, family demands, work-family conflict (WFC) and family-work conflict (FWC). Sixty questionnaires were administered to employees in a government health training institution in Sarawak, Malaysia. Data were analyzed using SPPS version 17 and independent t-Test was employed in testing the hypotheses. The study found that men and women are significantly different in terms of supervisor support, work-family conflict and family demands. However, there was no significant difference between men and women employees with regard to work demands, family-work conflict and utilization of family-friendly policies. In line with previous Western findings, women experienced higher level of work to family conflict (WFC) than men employees. In addition, women also reported higher family demands than men. These findings strengthened the traditional gender role ideology ascribed by majority of Malaysians and lend support to the gender role theory. Therefore, the organization could provide relevant training, such as, time and stress management. Supervisors could be trained to be more aware of work-family balance issues faced by their employees and assist them accordingly.